The best we've been - Vogt, Beth K. (Vogt, Beth K. Thatcher sisters, 2020)
"How can you choose what is right for you when your decision will break the heart of someone you love? Having abandoned her childhood dream years ago, Johanna Thatcher knows what she wants from life. Discovering that her fiancé was cheating on her only convinces Johanna it's best to maintain control and protect her heart. Despite years of distance and friction, Johanna and her sisters, Jillian and Payton, have moved from a truce toward a fragile friendship. But then Johanna reveals she has the one thing Jillian wants most and may never have--and Johanna doesn't want it. As Johanna wrestles with a choice that will change her life and her relationships with her sisters forever, the cracks in Jillian's marriage and faith deepen. Through it all, the Thatcher sisters must decide once and for all what it means to be family."--